2000
DOI: 10.1046/j.1365-2389.2000.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Myriapod and isopod communities in soils contaminated by heavy metals in northern France

Abstract: Summary Soil invertebrates suffer from contamination of the soil by heavy metals. We have studied the effects of contamination by cadmium, zinc and lead on their communities in soils in northern France by comparing polluted land with non‐contaminated sites. We have followed the seasonal variations and effects of soil properties. Saprophagous invertebrates (Diplopoda, Isopoda) and Chilopoda were sampled by pitfall‐trapping from February to November in fairly contaminated areas. In addition, a Berlese extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 14 publications
2
21
0
3
Order By: Relevance
“…The slow down of the organic matter degradation in soils around Umicore can be induced by the higher contamination levels and/or by the more frequent waterlogging in this area. It was shown that high concentrations of Cd, Pb and Zn around the two smelters strongly affected the ecosystem functioning by reducing the biodiversity and especially the terrestrial macroinvertebrates (Grelle et al 2000;Nahmani and Rossi 2003) and thus disturbing the carbon cycle. Waterlogging of the soils around Umicore is related to an alluvial characteristic and to the presence of the ground water rising at the soil surface during the wet season and especially in winter.…”
Section: Physico-chemical Characteristics Of Urban Soilsmentioning
confidence: 99%
“…The slow down of the organic matter degradation in soils around Umicore can be induced by the higher contamination levels and/or by the more frequent waterlogging in this area. It was shown that high concentrations of Cd, Pb and Zn around the two smelters strongly affected the ecosystem functioning by reducing the biodiversity and especially the terrestrial macroinvertebrates (Grelle et al 2000;Nahmani and Rossi 2003) and thus disturbing the carbon cycle. Waterlogging of the soils around Umicore is related to an alluvial characteristic and to the presence of the ground water rising at the soil surface during the wet season and especially in winter.…”
Section: Physico-chemical Characteristics Of Urban Soilsmentioning
confidence: 99%
“…Direct and indirect effects of heavy metal pollution on the soil fauna have been observed and demonstrated experimentally (Bengtsson et al ., 1983; Hågvar & Abrahamsen, 1990; Grelle et al ., 2000). Such impacts have far‐reaching consequences on the processes of humification and mineralization and on the development of humus forms (Ponge, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We aimed in this study to assess the impact of heavy metal pollution on humus profiles and soil biogenic structures. Since we know that in the north of France communities of macroinvertebrates are severely affected by high levels of heavy metal deposition (Grelle et al ., 2000), we hypothesize that changes in humus form occur under direct (toxicity) and indirect (changes in litter composition) effects of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 1997;Witzel, 1998;Hames and Hopkin, 1991;Bibic\ et al, 1997, metal toxicity (Joosse et al, 1981, 1983Crommentuijn et al, 1994;Drobne and Hopkin, 1995;Drobne and Strus, 1996;Abdellateif et al, 1998;Coenen-Stass, 1998;Knigge and KoK hler 2000); or incidence in extremely contaminated environment (Hopkin and Hames, 1994;Rabitsch, 1995). Some of the studies monitored woodlice in extremely contaminated area like smelters and mines (Grelle et al, 2000;Rabitsch, 1995;Hopkin and Hames, 1994); the others were performed under laboratory conditions. There are no studies devoted to low-level contamination or natural lead and cadmium in the environment and their relation to the level in isopods.…”
Section: Introductionmentioning
confidence: 99%